Strategi Pengelolaan Sampah Secara Terpadu (Studi Kasus : Kabupaten Bekasi) - Yeyen Ekawati; kasman (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2024)
The waste management issue has also become a serious concern in Indonesia. According to data from the Ministry of Environment and Forestry (KLHK) in 2020, Indonesia produces approximately 67.8 million tons of waste per year, with the largest composition being organic waste (60%) and plastic waste (15%) (KLHK, 2020). However, the existing waste management system still faces various challenges, such as low public participation in waste management, lack of waste management infrastructure, and limitations in recycling technology utilization. The method used in this study is a qualitative descriptive analysis method. Based on the data obtained, processed, and presented spatially, there are several sub-districts that have not yet been served with waste management facilities, including Muaragembong, Cabangbungin, Sukawangi, Sukakarya, Pebayuran, Serang Baru, and Cibarusah sub-districts. The capacity of Temporary Waste Storage Sites (TPS) in Bekasi Regency is dominated by insufficient capacity, so there is still a need to add 120 TPS with a capacity of 10 tons/day, distributed across all sub-districts in Bekasi Regency. The capacity of 3R TPS (Reduce, Reuse, Recycle) is already sufficient, but the distribution is still uneven across all sub-districts in Bekasi Regency, resulting in some sub-districts still being underserved. The results of the SWOT analysis and the calculation of internal and external factors indicate that the strategy to address the waste management issues in Bekasi Regency falls under an aggressive strategy, which is to leverage strengths to seize existing opportunities